Balloon-Assisted Percutaneous Thrombin Injection for Treatment of Iatrogenic Left Subclavian Artery Pseudoaneurysm in a Critically Ill COVID-19 Patient - Hassan Al-Thani; Ahmed Hussein; Ahmed Sadek; Ali Barah; Ayman El-Menyar (Case Reports in Vascular Medicine)
Background. Central venous catheter represents an important tool in the management of critically ill patient. In this report, we described a COVID-19-positive case who had COVID-related complications and iatrogenic left subclavian artery pseudoaneurysm after central venous catheter insertion. Case Presentation. A 58-year-old male patient presented with a high-grade fever, myalgia, and shortness of breath due to COVID-19 infection. He required mechanical ventilation support and hemodialysis. He also developed uneventful deep vein thrombosis and myocardial infarction. As a complication of central line insertion, the patient developed pseudoaneurysm that originated from the subclavian artery with significant bleeding and large hematoma. Balloon-assisted percutaneous thrombin injection was done under ultrasound guidance. The patient was extubated 2 days later with no evidence of flow in the pseudoaneurysm. However, he lost movement in the left arm secondary to the compression of the brachial plexus from the pseudoaneurysm/hematoma, and therefore, 1.5 litres of the hematoma was evacuated in the operating room through a lateral left chest wall incision along the anterior axillary line to relieve the compression over the brachial plexus. The patient declined surgical reconstruction of the brachial plexus, and the flaccid paralysis of the arm did not recover during the follow-up. Conclusion. This is a case of unusual complications of COVID infection and iatrogenic left subclavian artery pseudoaneurysm postcentral vein cannulation. Balloon-assisted percutaneous thrombin injection for treatment of left subclavian artery pseudoaneurysm is feasible; however, delayed diagnosis could be associated with long-term or permanent disability.